Kesiapan Sekolah pada Implementasi Program Merdeka Belajar di Sekolah Menengah Atas Menuju Era Society 5.0 - Bayu Wisnanda; Riki Anggara Putra; Dahlia Dahlia; Afriadi Ramadhani Rakhman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to analyse how the readiness of senior high schools in implementing the independent learning program towards the era of society 5.0. The method in this research uses a qualitative literature study with a focus on the discussion of the independent curriculum and the independent learning programme. Data collection techniques were carried out by identifying and analysing literature from 10 national and 5 international journals, as well as independent learning policy guidelines through the Ministry of Education and Culture, state laws and regulations and internet readings. The results of this study formulate how to deal with society 5.0 in education: The government must try to increase equitable development and openness to expand internet connections throughout Indonesia; The government must be able to synchronise education and industry so that later college and school graduates can work in their fields and in accordance with the criteria needed by industry to reduce unemployment in Indonesia in the future. The positive aspects of the independent learning programme are that teachers are more free to be creative in teaching as much as possible and get to know the interests, talents, needs, and abilities of students. Good cooperation between teachers, school administrators, agencies, parents, and other stakeholders in the independent learning programme can accelerate the achievement of the goals of the national education system. Keywords: Social Era 5.0, Independent Learning Curriculum, Senior High School